Variasi Konsentrasi Nutrien dan Dampaknya terhadap Kelimpahan Fitoplankton di Perairan Teluk Semarang - Jati, Oktavianto Eko; Afiati, Norma; Purnomo, Pujiono Wahyu; Ayuningrum, Diah; Dewi, Desca Estiyani (Jurnal Laut Khatulistiwa, 2026)
Phytoplankton are important microorganisms in water ecosystems. They help in the nutrient cycle. Nutrients in water affect how many and what types of phytoplankton are present. This also impacts the fertility of coastal waters like Semarang Bay, which are influenced by human activities. This study looks at the link between water nutrients, phytoplankton, and water fertility. The study used a descriptive, quantitative method on November 10, 2024, at 6 chosen locations. Measurements taken on-site included DO, temperature, salinity, pH, and transparency. Lab tests looked at phytoplankton types, chlorophyll-a, silica, nitrate, nitrite, orthophosphate, and TSS using SNI and APHA methods. The main phytoplankton types were Diatoms, Dinoflagellates, and Cyanobacteria (26 types), with Chaetoceros being the most common (1,598 cells/L). Bacteriastrum and Chaetoceros were seen most often. Environmental data showed temperatures from 29.2–33.3°C, pH 8.6–8.8, DO 5.3–7.3 mg/L, salinity 32–33‰, and water clarity 0.55–5.97 m; chlorophyll-a 1.55–8.85 µg/L. TSS levels were 18.58–38.94 mg/L, nitrate 1.3–1.9 mg/L, nitrite 0.01–0.02 mg/L, and phosphate 0.8 mg/L, with the highest silica at Station 4. PCA analysis showed a productivity pattern (PC1) that was positively associated with chlorophyll-a, phytoplankton numbers, silica, and dominance, but negatively associated with TSS, nitrate–nitrite, and transparency. This means silica helps diatom growth, while high TSS can reduce productivity by blocking light, even though it might bring nutrients.